Establishing Dermatologic Care for the Homeless and Underserved at a Student-Run Clinic - Teal, Lindsey; Spitz, Katherine; Diven, Dayna (Journal of Student-Run Clinics, 2020)
Skin problems are the reason one-third of people experiencing homelessness seek medical care. These conditions are exacerbated by increased exposure to the sun and hazardous environments, malnutrition, physical injuries, and limited access to health care. This is a medically vulnerable population that does not have regular access to specialty care, such as dermatologic care. The objective of this pilot project was to increase access to dermatologic care in the homeless and underserved populations by integrating dermatologic specialists into a student-run clinic. Dermatologic screenings were held at a local student-run clinic monthly. Medical students and dermatologists screened patients for any dermatologic findings and educated patients on skin care and self-screening methods. Afterward, social work students referred patients to local dermatologists that best fit their needs. Patient demographics, skin findings, and qualitative patient responses were recorded. The majority of patients were interested in being screened, as many had never been evaluated by a dermatologist. Many felt the timing and location of the clinic was helpful in obtaining care. All patients successfully taught back skin cancer prevention methods. All skin findings were benign. This experience demonstrates that integrating dermatology specialists into an interprofessional, student-run clinic to provide dermatologic screenings and skin care education can be accomplished. Further studies will evaluate integrating monthly dermatology care at clinic as well as piloting the integration of other medical specialties into the clinic, such as ophthalmology.